PENGARUH PERLAKUAN TAX AMNESTY DAN PENERAPAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK (Studi pada UMKM Yang Terdaftar di KPP Pratama Batu) - Amelda Amelda; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis research was conducted with the aim of analyzing the effect of tax amnesty treatment and the application of e-filing on taxpayer compliance (a study on registered MSMEs at KPP Pratama Batu). The sample in this study is the UMKM taxpayers who are registered at KPP Pratama Batu who already have an NPWP and are registered at KPP Pratama Batu. Based on data collection, a total of 75 respondents were obtained, with the data collection method used, namely using the Slovin formula. Based on the results of simultaneous testing, it shows that the tax amnesty and e-filing variables affect the compliance of MSME taxpayers. The partial test results show that the tax amnesty and e-filing variables have a positive effect on MSME Taxpayer Compliance.Keywords : Tax Amnesty, E-filing and UMKM Taxpayer Compliance